Ethyl acetate layer of a methanol extract from Aquilaria crassna promotes oxidative stress-mediated apoptosis in non-small-cell lung cancer cells - Kim, Kwang-Youn; Hwang, You Lim; Park, Kwang Il; Ahn, Soon-Cheol (Molecular & cellular toxicology, 2024)
Background Chemotherapy is the cornerstone for treating most types of cancer; however, it has a variety of side effects and tumor cells can become resistant to its effects. To overcome these obstacles, natural products have been used as an alternative to selectively target cancer cells without affecting normal cells. They are effective and safe, even at low doses. Aquilaria crassna has been traditionally used as an herb to treat allergies, diabetes, and neurological disorders; however, the molecular mechanisms associated with the anti-cancer effects of Aquilaria crassna extracts are unknown. Objective In this study, we evaluated extracts from wood chips of A. crassna prepared with various solvents. We determined whether the ethyl acetate layer of a methanol extract from A. crassna (ACM/E) could induce apoptosis in lung cancer cells and elucidated the underlying mechanisms. Results ACM/E treatment reduced lung cancer cell viability and the morphology changed to a spherical shape in a dose-dependent manner. In addition, ACM/E increased the ratio of apoptotic cells, cleavage of apoptotic-related proteins (caspase-3 and PARP) and intracellular reactive oxygen species (ROS) generation. In particular, apoptotic cell death of ACM/E-treated NCI-H889 and HCC1833 cells was more pronounced compared with that in A549 cells and occurred in a dose-dependent manner. Pre-treatment with N-acetyl-L-cysteine (NAC), a ROS inhibitor, restored ACM/E-induced production of ROS, and resulted in the restoration of mitochondrial membrane potential and apoptosis in NCI-H889 cells. Conclusion Taken together, these findings suggest that ACM/E from A. crassna induces ROS-mediated apoptosis in NCI-H889 small-cell lung cancer cells and represents a novel therapeutic agent for intractable lung cancer.